Structure–activity relationship in the passage of different pyrrolizidine alkaloids through the gastrointestinal barrier: ABCB1 excretes heliotrine and echimidine. Issue 5 (27th December 2013) - Hessel, Stefanie; Gottschalk, Christoph; Schumann, Dania; These, Anja; Preiss‐Weigert, Angelika; Lampen, Alfonso
<x xml:space="preserve">Abstract</x> Scope 1, 2‐Unsaturated pyrrolizidine alkaloids (PA) are found in plants such as Asteraceae and Boraginaceae families. Acute PA poisoning via contaminated food or feed causes severe damage to liver depending on species‐specific oral bioavailability. For assessing PA bioavailability, their passage across the intestinal barrier was investigated using Caco‐2 cells. Methods Differentiated Caco‐2 cells were exposed in transport chambers to the PA heliotrine (Hn), echimidine (Em), senecionine (Sc), and senkirkine (Sk). Cell supernatants were analyzed by LC‐MS/MS. Results PA pass Caco‐2 monolayer from the apical into basolateral compartment depending on their chemical structure. Compared to the cyclic diesters Sc and Sk with a passage rate of 47% ± 4 and 40% ± 3, respectively, the transferred amount of the monoester Hn (32% ± 3) and open‐chained diester Em (13% ± 2) was substantially lower. This suggested an active transport of Hn and Em. Using Madin–Darby canine kidney II/P‐glycoprotein (ABCB1)‐overexpressing cells, the active excretion of Hn and Em by ABCB1 from the gastrointestinal epithelium into the gut lumen was shown. Conclusion PA cross the intestinal barrier structure‐dependently. The passage of the noncyclic PA Hn and Em is reduced by an ABCB1‐driven efflux into the gastrointestinal lumen resulting in a decreased oral bioavailability.